2019
DOI: 10.3390/urbansci3010026
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use/Land-Cover Change Analysis and Urban Growth Modelling in the Greater Accra Metropolitan Area (GAMA), Ghana

Abstract: A rapid increase in the world’s population over the last century has triggered the transformation of the earth surface, especially in urban areas, where more than half of the global population live. Ghana is no exception and a high population growth rate, coupled with economic development over the last three decades, has transformed the Greater Accra region into a hotspot for massive urban growth. The urban extent of the region has expanded extensively, mainly at the expense of the vegetative cover in the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 27 publications
7
78
0
Order By: Relevance
“…Census data show that between 1984 and 2010, Kumasi's population increased with a growth rate of over 5% per annum [39], making it one of the fastest growing cities in Ghana [43] and implying an expansion of the built-up area [44]. The changes observed in the Owabi catchment are consistent with those observed in many studies conducted at national and regional levels in Ghana [6,41,[45][46][47]. For example, using a mixed-method approach, Kleeman et al [6] identified population growth as a major driver of land use and land cover changes in Ghana's Upper East region.…”
Section: Discussionsupporting
confidence: 75%
“…Census data show that between 1984 and 2010, Kumasi's population increased with a growth rate of over 5% per annum [39], making it one of the fastest growing cities in Ghana [43] and implying an expansion of the built-up area [44]. The changes observed in the Owabi catchment are consistent with those observed in many studies conducted at national and regional levels in Ghana [6,41,[45][46][47]. For example, using a mixed-method approach, Kleeman et al [6] identified population growth as a major driver of land use and land cover changes in Ghana's Upper East region.…”
Section: Discussionsupporting
confidence: 75%
“…Like other anthropogenic-environmental interactions, urban LULC changes are due to a myriad of factors, as no single factor can account for these changes. The interactions are different in every region, but most scholars agree that most LULC changes are influenced by specific economic, demographic, socio-political and environmental conditions [8,9]. These factors are usually interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a number of studies have presented city-wide land-cover maps of Accra based on medium-and high-resolution images (see [14][15][16][17][18] for recent examples). So far only a few studies have analyzed the challenges of comparing the maps resulting from different remote sensing-based studies.…”
Section: Introductionmentioning
confidence: 99%